Effect of solvent types on structure and performance of polyethersulfone nanofiltration membrane in monovalent and divalent ions separation - Hasbullah, Hasrinah; Ismail, Ahmad Fauzi; Ng, B. C.; Abdullah, M. S. (2005)
membrane produced using NMP as the solvent followed by DMAc and lastly, DMF. This study indicated that solvent with higher boiling point (in this study, NMP has the highest boiling point) produced a desired NF in embrane with more finger-like structure. The diameters of pores in skin layer were measured by Steric-Hindrance Pore (SHP) and Teorell-Meyer-Sievers (TMS) model. The mean pore size of each produced membrane was about 1.28 ring 1.47 nm and 1.59 nm for AWP, DMAc and DMF respectively. The performances of the PES nanofiltration membranes were examined based an rejection and flux. Generally, the rejections of mono and divalent anions were identified to be within 29%-38%, and 81%-91% respectively. As predicted by the morphological structure, NMP solvent-membrane showed the best salt rejection for both monovalent and divalent ions as compared to DMAc and DMF. Hence, solvent was discovered to affect the morphological structure and consequently, improved the performance of the polyethersulfone nanofiltration membrane.